Polyhydroxyalkanoate (PHA) production using waste vegetable oil by Pseudomonas sp. strain DR2 - Song, J.H. (Korea University, Seoul, Republic of Korea); Jeon, C.O. (Chung-Ang University, Seoul, Republic of Korea); Choi, M.H. (Gyeongsang National University, Jinju, Republic of Korea); Yoon, S.C. (Gyeongsang National University, Jinju, Republic of Korea); Park, W.J. (Korea University, Seoul, Republic of Korea), E-mail: wpark@korea.ac.kr (Journal of microbiology and biotechnology, 2008)
To produce polyhydroxyalkanoate (PHA) from inexpensive substrates by bacteria, vegetable-oil-degrading bacteria were isolated from a rice field using enrichment cultivation. The isolated Pseudomonas sp. strain DR2 showed clear orange or red spots of accumulated PHA granules when grown on phosphate and nitrogen limited medium containing vegetable oil as the sole carbon source and stained with Nile blue A. Up to 37.34% (w/w) of intracellular PHA was produced from corn oil, which consisted of three major 3-hydroxyalkanoates; octanoic (C8:0, 37.75% of the total 3-hydroxyalkanoate content of PHA), decanoic (C10:0, 36.74%), and dodecanoic (C12:0, 11.36%). Pseudomonas sp. strain DR2 accumulated up to 23.52%) (w/w) of PHA∧MCL from waste vegetable oil. The proportion of 3-hydroxyalkanoate of the waste vegetable-oil-derived PHA [hexanoic (5.86%), octanoic (45.67%), decanoic (34.88%), tetradecanoic (8.35%), and hexadecanoic (5.24%,)] showed a composition ratio different from that of the corn-oil-derived PHA. Strain DR2 used three major fatty acids in the same ratio, and linoleic acid was the major source of PHA production. Interestingly, the production of PHA in Pseudomonas sp. strain DR2 could not occur in either acetate- or butyrate-amended media. Pseudomonas sp. strain DR2 accumulated a greater amount of PHA than other well-studied strains (Chromobacterium violaceum and Ralstonia eutropha H16) when grown on vegetable oil. The data showed that Pseudomonas sp. strain DR2 was capable of producing PHA from waste vegetable oil.